1993
DOI: 10.1089/end.1993.7.11
|View full text |Cite
|
Sign up to set email alerts
|

Perirenal Hematomas Caused by SWL with EDAP LT-01 Lithotripter

Abstract: A total of 419 calculi in the upper urinary tract of 402 patients were treated by SWL with the EDAP LT-01 lithotripter from July 1988 to September 1989. Subcapsular hematomas resulted in 17 kidneys of 16 patients, an incidence of 4.1%. On CT scan, fractures with subcapsular hematomas were observed in nine kidneys, and a retroperitoneal hematoma was observed in one patient. There was no significant difference in stone location and size, grade of hydronephrosis, number of shock waves, applied energy, or post-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Indeed, patient studies have suggested that focal width can affect outcomes with lower stone‐free rates for narrow focal width lithotriptors [18–22]. Focal width has also been implicated in SWL injury, with the suggestion of an increased occurrence of adverse effects with narrow focal width machines [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, patient studies have suggested that focal width can affect outcomes with lower stone‐free rates for narrow focal width lithotriptors [18–22]. Focal width has also been implicated in SWL injury, with the suggestion of an increased occurrence of adverse effects with narrow focal width machines [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] In addition, laboratory studies have shown that the renal lesion produced by a narrow focal width lithotripter can be more intense than that produced by a wider focal width machine, and clinical reports have suggested that a narrow focal width may be linked to an increase in the occurrence of adverse effects. [15][16][17] Previously, we undertook an evaluation of the XiXin CS2012 (or XX-ES) lithotripter. 18 This lithotripter represents a novel concept, a departure from the higher pressure, narrower focal width lithotripters that are most commonly in use.…”
mentioning
confidence: 99%
“…The first reports of hematoma associated with aspirin therapy were in 1990; one patient was described as taking ''two aspirins per day'' before SWL and needed surgical evacuation, 60 while the other stopped aspirin 10 days before treatment and was treated conservatively. 61 A further three series have reported on antiplatelet therapy; in a small series, two of nine patients with haematomas were receiving aspirin up to treatment; 62 in a series of 402 patients, 16 subcapsular hematomas were found with a significant correlation to antiplatelet therapy; 63 and in the largest series of 31 hematomas, only one patient was receiving aspirin therapy. 58 In these studies the patients reported presented with symptomatic hematoma and do not reflect the true incidence of all hematoma; therefore, it is difficult to surmise the true effect of antiplatelet therapy.…”
Section: Coagulation and Plateletsmentioning
confidence: 99%